Leadership 2030 : the six megatrends you need to understand to lead your company into the future - Vielmetter, Georg (AMACOM, 2014)
The tumultuous changes of the past decade, including China's economic rise and the financial meltdown, were just the beginning. The next cataclysmic wave is surging relentlessly ahead, demanding leaders who can steer their companies through complexity and change. Drawn from original research conducted jointly with foresight company Z-Punkt and further analyzed by Hay Group, Leadership 2030 uncovers six megatrends that will dramatically impact organizations' markets, cultures, systems, and processes:1. Globalization 2.0: Asia dominates the global economy; 2. Climate change: Sustainability becomes imperative; 3. Individualism: Freedom of choice erodes loyalty; 4. Digitization: Boundaries blur between private and working lives; 5. Demographic changes: Aging populations intensify the talent war; 6. Converging technologies: The sharpest tech shift in history is around the corner. Research findings and case studies provide compelling evidence of each megatrend and highlight the skills, capabilities, and attitudes leaders must cultivate, such as adaptability, collaboration, cultural sensitivity, strategic thinking, meaning creation, and more. In the rush to produce quarterly profits in chaotic conditions, the longer view is often obscured. This forward-thinking book helps businesses everywhere prepare for the seismic changes on the horizon.